Pemanfaatan Aplikasi Pembelajaran sebagai Media Intervensi bagi Anak Berkebutuhan Khusus - Tengku Ryan Hidayatullah; Sri Nurhayati Selian (Yayasan Syamil Quran Nunukan, 2026)
Children with special needs are a group of children whose developmental characteristics differ from those of typically developing children, thereby requiring educational, psychological, and social services tailored to their specific needs. The term